Peramalaan Permintaan Ayam Menggunakan Metode Penghalusan Eksponensial Sederhana pada UMKM Ayam Geprek Rizky Baru - Juarsa, Rahmadini Payla; Kuniawan, Andry; Nurtani, Anjelina; Nainggolan, Ledy Pretty; Takifa, Adrina; Rasyid, T. Afnan; Aldino, Zulvani Dwi (STMIK Sinar Nusantara, 2024)
Demand forecasting is crucial to ensure customer demands are met and the company does not experience shortages or surpluses of raw materials. Ayam Geprek Rizky Baru, a business that produces spicy fried chicken, currently relies solely on the owner's intuition to determine production and raw material stock. This often leads to mismatches with actual customer demand patterns. This study aimed to calculate chicken demand forecasts using a more quantifiable method, specifically the simple exponential smoothing method. The study used historical sales data from 2023 to forecast chicken demand for January 2024. The alpha values used were 0.1 and 0.2, with evaluation methods including MAD (Mean Absolute Error), MSE (Mean Square Error), and MAPE (Mean Absolute Percentage Error). The results indicated that an alpha value of 0.1 was better for forecasting chicken demand as it produced average MAD of 511.6782, MSE of 357263.36, and MAPE of 12.16%. Exponential smoothing using α = 0.1 resulted in a forecasted chicken demand for Ayam Geprek Rizky Baru in January 2024 of 4315.3064, or approximately 4316 pieces of chicken.